Complications and Impact on Quality of Life of Vertical Rectus Abdominis Myocutaneous Flaps for Reconstruction in Pelvic Exenteration Surgery. Issue 9 (September 2020) - van Ramshorst, Gabrielle H.; Young, Jane M.; Solomon, Michael J.
Abstract : BACKGROUND: Pelvic exenteration for malignancy sometimes necessitates flap reconstruction. OBJECTIVE: This study's aim was to investigate flap-related morbidity. DESIGN: A prospective database was reviewed from 2003 to 2016. All medical charts, correspondence, and outpatient follow-up records up to May 2017 were reviewed. SETTINGS: This study was conducted at a tertiary referral unit. PATIENTS: Patients who underwent pelvic exenteration surgery were selected. INTERVENTIONS: Reconstruction was performed with a vertical rectus abdominis myocutaneous flap. MAIN OUTCOME MEASURES: Primary outcome was flap-related complications (short or long term >3 months). Secondary outcomes were hospital stay, readmission, mortality, and quality of life (Short Form-36, Functional Assessment of Cancer Therapy for patients with colorectal cancer). RESULTS: Of 519 patients undergoing pelvic exenteration surgery, 87 (17%) underwent flap reconstruction. Median follow-up was 20 months (interquartile range, 8–39 months). Median age was 60 years (interquartile range, 51–66). Flap-related complications were found in 59 patients (68%), with minor recipient-site complications diagnosed in 33 patients (38%). In the short term, 15 patients experienced major recipient-site complications (17%), including flap separation (n = 7) and partial (n = 3) or complete necrosis (n = 4). Flap removal was required in 1 patient. Obesity was the single independent risk factor for short-term flap-related complications ( p = 0.02). Hospital admission was significantly longer in patients with short-term major flap complications (median 65 days, p < 0.001) compared with patients without or with minor complications. There was no 90-day mortality. Patients who required flap reconstruction reported lower baseline quality-of-life scores than patients without flap reconstruction, but both recovered over time. In the long term, minor flap-related complications occurred in 12 patients, and 11 patients had major donor-site complications. Fourteen patients developed major recipient-site complications (16%), including sacral collections, enterocutaneous fistulas, perineal ulcer, or hernia. LIMITATIONS: This was a retrospective analysis of prospectively collected data. CONCLUSIONS: Vertical rectus abdominis myocutaneous flaps in pelvic exenteration surgery have a high incidence of morbidity that has significant impact on hospital stay and a temporary impact on quality of life. Flap reconstruction should be used selectively in pelvic exenteration surgery. See Video Abstract at http://links.lww.com/DCR/B274 . COMPLICACIONES E IMPACTO EN LA CALIDAD DE VIDA DE LOS COLGAJOS MIOCUTÁNEOS DE MUSCULO RECTO DEL ABDOMEN EN CASOS DE RECONSTRUCCIÓN DE EXENTERACIÓN PÉLVICA: ANTECEDENTES: La exenteración pélvica (EP) para malignidad a veces requiere reconstrucción con colgajos musculares. OBJETIVO: El propósito del presente estudio fue investigar la morbilidad relacionada con los colagajos musculares. DISEÑO: Revisión de una base de datos prospectiva de 2003-2016. Se evaluaron todas las historias clínicas, la correspondencia y los registros de seguimiento de pacientes ambulatorios hasta mayo de 2017. AJUSTES: Unidad de referencia terciaria. PACIENTES: Todos aquellas personas con cirugía de exenteración pélvica. INTERVENCIONES: Reconstrucción con colgajo miocutáneo de musculo recto vertical del abdomen. PRINCIPALES RESULTADOS: El resultado primario fueron las complicaciones relacionadas con el colgajo (a corto o largo plazo >3 meses). Los resultados secundarios fueron la estadía hospitalaria, la readmisión, la mortalidad y la calidad de vida (QOL; SF-36, FACT-C). RESULTADOS: De 519 pacientes sometidos a EP, 87 (17%) se sometieron a reconstrucción con colgajos miocutáneos. La mediana de seguimiento fue de 20 meses (RIC 8-39 meses). La mediana de edad fue de 60 años (IQR 51-66). Se encontraron complicaciones relacionadas con el colgajo en 59 pacientes (68%), con complicaciones menores en el sitio del receptor diagnosticadas en 33 pacientes (38%). A corto plazo, quince pacientes sufrieron complicaciones mayores en el sitio del receptor (17%), incluida la separación del colgajo ( n = 7), necrosis parcial ( n = 3) o necrosis completa ( n = 4). Se requirió la extracción del colgajo en un paciente. La obesidad fue el único factor de riesgo independiente para complicaciones relacionadas con el colgajo a corto plazo ( p = 0.02). El ingreso hospitalario fue significativamente mayor en pacientes con complicaciones de colgajos mayores a corto plazo (mediana 65 días p <0.001) en comparación con pacientes sin complicaciones menores o con complicaciones menores. No hubo mortalidad a los 90 días. Los pacientes que requirieron reconstrucción con colgajo informaron puntajes de calidad de vida basales más bajos que los pacientes sin reconstrucción con colgajo, pero ambos se recuperaron con el tiempo. A largo plazo, ocurrieron complicaciones menores relacionadas con el colgajo en 12 pacientes y 11 pacientes tuvieron complicaciones mayores en el sitio donante. Catorce pacientes desarrollaron complicaciones mayores en el sitio del receptor (16%), incluidas colecciones sacras, fístulas enterocutáneas, úlceras perineales o herniación. LIMITACIONES: Análisis retrospectivo de datos recolectados prospectivamente. CONCLUSIONES: Los colgajos miocutáneos del musculo recto vertical del abdomen en casos de cirugía de exenteración pélvica tienen una alta incidencia de morbilidad conllevando a un impacto significativo en la estadía hospitalaria y un impacto temporal en la calidad de vida. Las reconstrucciones con colgajos deben aplicarse muy selectivamente en la cirugía de exenteración pélvica. Consulte Video Resumen en http://links.lww.com/DCR/B274 .